2007
DOI: 10.1016/j.anihpb.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Aging for interacting diffusion processes

Abstract: We study the aging phenomenon for a class of interacting diffusion processes {X t (i), i ∈ Z d }. In this framework we see the effect of the lattice dimension d on aging, as well as that of the class of test functions f (X t) considered. We further note the sensitivity of aging to specific details, when degenerate diffusions (such as super random walk, or parabolic Anderson model), are considered. We complement our study of systems on the infinite lattice, with that of their restriction to finite boxes. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The ageing phenomenon has been extensively studied for disordered systems such as trap models and spin glasses; see [3] and references therein. In the context of the parabolic Anderson model, a certain form of ageing based on correlations was studied for some time-dependent potentials in [2,6], and it was shown that such systems exhibit no ageing. The recent paper [11] dealt with potentials from class (1) and studied the correlation ageing (which gives only indirect information about the evolution of localisation) and more explicit annealed ageing (which, in contrast to the quenched setting, is based on the evolution of the islands contributing to the solution averaged over the environment).…”
Section: Remarkmentioning
confidence: 99%
“…The ageing phenomenon has been extensively studied for disordered systems such as trap models and spin glasses; see [3] and references therein. In the context of the parabolic Anderson model, a certain form of ageing based on correlations was studied for some time-dependent potentials in [2,6], and it was shown that such systems exhibit no ageing. The recent paper [11] dealt with potentials from class (1) and studied the correlation ageing (which gives only indirect information about the evolution of localisation) and more explicit annealed ageing (which, in contrast to the quenched setting, is based on the evolution of the islands contributing to the solution averaged over the environment).…”
Section: Remarkmentioning
confidence: 99%
“…The term φ t (x) corresponds to the height of the interface at position x ∈ Z d and time t ≥ 0. In particular, we have a random walk representation of space-time correlations of this model (see [8], [12,Proposition 1.3]). Since the energy of the interface φ is determine by its height differences, this model is called the ∇φ interface model and its studies have been active in both of static and dynamic aspects (see [14] and references therein).…”
Section: Model and Resultsmentioning
confidence: 99%
“…Namely, asymptotics of the correlation ( (s, s + t)/ √ (s, s) √ (s + t, s + t)) as s, t → ∞ depends on the choice of s, t (see [8]). Namely, asymptotics of the correlation ( (s, s + t)/ √ (s, s) √ (s + t, s + t)) as s, t → ∞ depends on the choice of s, t (see [8]).…”
Section: Lemma 12mentioning
confidence: 99%
“…Further, there exists a random walk representation for the space-time correlations of (1.15) (c.f. [DD,Deu2]; see also the references therein for other interacting diffusion processes admitting a random walk representation for their correlations). From this random walk representation we have that the covariance of the centered Gaussian process g t := φ t (0) is…”
Section: Introductionmentioning
confidence: 99%